The Economic Impact of Digital Nomads’ Loyalty to Co-Working Spaces in Canggu Village - Suparna, I Komang; Mahyuni, Luh Putu (International Journal of Economics Development Research (IJEDR), 2024)
Digital nomads in Bali face several issues, despite the island's popularity as a hub for remote work. Digital nomads often struggle with understanding and navigating Indonesia's visa requirements, which may not clearly accommodate remote workers. This uncertainty can lead to legal issues or unexpected expenses. This research design uses a quantitative approach with the research location conducted at co-working spaces in Canggu, North Kuta District, Badung Regency, Bali. Data analysis uses the Partial Least Squares (PLS) technique. The results of the data analysis show customer satisfaction acts as a partial mediating variable in the relationship between service quality and revisit intention. This means that while service quality can directly influence revisit intention, it can also do so through customer satisfaction, albeit not entirely. Similarly, social value serves as a partial mediating variable between service quality and revisit intention. This indicates that service quality can directly impact revisit intention without necessarily involving social value.